Prospects for the application of infectious virus detection technology based on propidium monoazide in African swine fever management - Zeng, Dexin; Qian, Bingxu; Li, Yunfei; Zong, Kai; Peng, Wanqing; Liao, Kai; Yu, Xiaofeng; Sun, Juanjuan; Lv, Xiaying; Ding, Liu; Wang, Manman; Zhou, Tingting; et al. (Frontiers in Microbiology, 2022)
African swine fever (ASF) is a hemorrhagic and often fatal disease occurring in domestic pigs and wild boars. ASF can potentially greatly impact the global trade of pigs and pork products and threaten global food security. Outbreaks of ASF must be notified to the World Organization for Animal Health. In this study, we analyzed the feasibility of applying propidium monoazide (PMA) pretreatment-based infectious virus detection technology to ASF prevention and control and investigated the prospects of applying this technology for epidemic monitoring, disinfection effect evaluation, and drug development. PMA as a nucleic acid dye can enter damaged cells and undergo irreversible covalent crosslinking with nucleic acid under halogen light to prevent its amplification. Although this technology has been widely used for the rapid detection of viable bacteria, its application in viruses is rare. Therefore, we analyzed the theoretical feasibility of applying this technology to the African swine fever virus (ASFV) in terms of gene and cell composition. Rapid infectious ASFV detection technology based on PMA pretreatment would greatly enhance all aspects of ASF prevention and control, such as epidemic monitoring, disinfection treatment, and drug development. The introduction of this technology will also greatly improve the ability to prevent and control ASF.